2017
DOI: 10.1002/ejp.1018
|View full text |Cite
|
Sign up to set email alerts
|

Slow brushing reduces heat pain in humans

Abstract: Slow brushing stimuli - optimal for activation of C-tactile fibres - can reduce pain from cutaneous heating. No such effect was seen with fast brushing or vibration. These observations indicate the role of C-tactile fibres in pain modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 62 publications
3
76
1
Order By: Relevance
“…However, we found no significant effect during hand grip and that may have been due to competing effects. In contrast to a previous investigation on heat pain (Liljencrantz et al 2017), the addition of CT-optimal stimulation by brushing was not sufficient to reduce pain from muscle fatigue in our hand-grip task. However, we found that MSNA burst area was significantly lower during brushing than warmth.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found no significant effect during hand grip and that may have been due to competing effects. In contrast to a previous investigation on heat pain (Liljencrantz et al 2017), the addition of CT-optimal stimulation by brushing was not sufficient to reduce pain from muscle fatigue in our hand-grip task. However, we found that MSNA burst area was significantly lower during brushing than warmth.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there is a dearth of knowledge on the potential pain modulatory effects of somatosensory stimuli with a different valence, notably pleasant stimuli via the activation of CT afferents, and how it may activate pain modulatory mechanisms in the oro‐facial region. This should be an increasing area of interest, particularly as it was recently demonstrated that a stimulus considered affectively more pleasant resulted in a greater reduction of pain 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…It was thought that the result would be that unmyelinated mechanoreceptors reacted, not the myelinated afferents [17]. On the other hand, with touching at a fast speed, it was thought that unmyelinated mechanoreceptors would be less activated [18]. Therefore, a therapist applied gentle touching with both hands from the top to the bottom of the back of an experiment participant at the speed of 3 to 5 cm per second.…”
Section: Methods Of Touching and A Therapistmentioning
confidence: 99%
“…C-tactile fibers are reported to enhance relaxation of the mind and the body, and the optimum stroking can be beneficial [16]. C-tactile fibers are most activated by smooth and soft touching [17,18]. C-tactile fibers are less activated by a quick motion of touching.…”
Section: Purpose Of the Researchmentioning
confidence: 99%